Comparison among the physical properties of calcium phosphate‐based bone substitutes of natural or synthetic origin. Issue 4 (22nd January 2018) - Maté Sánchez de Val, José; Mazón, Patricia; Piattelli, Adriano; Calvo‐Guirado, José; Mareque Bueno, Javier; Granero Marín, José; De Aza, Piedad
Abstract: The aim of this study was to evaluate the influence of variations of the physical properties in the integration process of biomaterials. The biomaterials examined included two commercial grafting materials: bovine bone substitute material (Hypro‐oss ®, BioImplon GMbH, Gieben, Germany) and porcine bone substitute material (Osteobiol ®, Tecnoss, Torino, Italy); and synthetic tricalcium phosphate and hydroxyapatite (HA). Materials were first characterized, microstructure, composition of the graft, quantitative analyses, and X‐ray Spectroscopy (EDX) was determined. The microstructure of the both synthetic materials is very similar and different in comparison with organic‐derived materials. The four materials under study have a similar porosity divided between intra and interparticles porosity. Higher density was measured for the synthetized materials. The HA porcine has the lower due to the content of collagen in the material. All the materials have high porosity and high crystallinity; except Porcine, having a lower crystallinity due to the presence of collagen mixed with HA. Pore size was very similar for all the studied materials.